RECONSTRUCTION OF CONTEXTUAL LEARNING MODEL BASED ON LOCAL WISDOM IN SHARPENING CRITICAL THINKING - Diana, Rizki; Alfiatur Rohmaniyah; Rahmat Kamal (JURNAL PENDIDIKAN GLASSER, 2025)
Education in the modern era faces great challenges in preparing generations that are adaptive to global changes without losing their cultural identity. Local wisdom in Indonesia has the potential as an alternative source of knowledge that can enrich the learning process and improve students' critical thinking skills. This study aims to Implementation of the reconstruction of a contextual learning model based on local wisdom in enhancing critical thinking skills. Using a qualitative meta-synthesis method, this study analyzed 25 scientific articles published between 2017-2025 using thematic coding techniques and researcher triangulation to ensure the validity of the results. The analysis identified five forms of local wisdom integration: cultural artifact-based (28%), local narrative (24%), social practice (20%), local ecological knowledge (16%), and local philosophy (12%). In addition, four critical thinking development mechanisms were found, namely recontextualization (76%), cognitive confrontation (68%), identity construction (60%), and social transformation (52%). Based on these findings, this study developed a reconstructive model of contextual learning based on local wisdom with five main components: (1) Complexity of local wisdom integration in contextual learning, (2) Reconceptualization of critical thinking in the context of local wisdom, (3) Theoretical and practical implications, (4) Implementation challenges and limitations of the model, and (5) Limitations of the research study. This research confirms the need for more inclusive critical thinking indicators as well as improving educators' skills in facilitating epistemological dialog. Thus, this model not only strengthens cultural identity but also builds more contextualized and meaningful critical thinking for students.